Developments in participatory methods for software development - (:unkn) unknown (My University, 2015)
This paper briefly discusses the concept of Participatory design. Whereas the embodying research is in software engineering and development of large enterprise information systems, this paper discusses the general concepts of participation from a perspective of a developing country’s possible gains from embracing this methodological approach. In line with the theme of the conference “Emerging technologies and trends and the future of ICT Sector in Kenya” the content is abridged to reflect the wide spectrum of the audience in the conference
Paper presented at ICT confrence of 2006
This paper briefly discusses the concept of Participatory design. Whereas the embodying research is in software engineering and development of large enterprise information systems, this paper discusses the general concepts of participation from a perspective of a developing country’s possible gains from embracing this methodological approach. In line with the theme of the conference “Emerging technologies and trends and the future of ICT Sector in Kenya” the content is abridged to reflect the wide spectrum of the audience in the conference
Keywords: Software development--Africa; Software development--Kenya